A Comparative Study on the Knowledge and Usage Assessment of the Over the Counter Medications among Students from Tikrit University - Yasir Al-Radeef, Mohanad (Tikrit Journal of Pharmaceutical Sciences, 2023)
Introduction: Over the counter medicines are effective and safe remedies that can be usedwithout a prescription and their usage by students has been increased worldwide due to stressof exams and work pressure. Aim: To compare the knowledge and usage of these medicinesby students and to analyze the role of pharmacists in the practice of these drugs. Materialsand Methods: 450 students from 9 different colleges in Tikrit University were participated inthis cross sectional descriptive study. They were grouped into three groups; medical collegesgroup, scientific colleges group, and literary colleges group with 150 students in each group.Study was questionnaire based, and the results were analyzed by descriptive statisticalmethods. Results: Only 330 students were preferred to use these medications and thepreference was high among medical colleges' students. The remaining students wereexcluded. Popularity and adequate efficacy of these drugs were the main reasons for thepreference of these medications that were utilized in the treatment of minor conditions. Also57.6% of students were usually followed the pharmacist's advice regarding the appropriatechoice of preferred drug, while the remaining were followed physician's advice. Two thirds ofstudents received full instructions regarding the use of preferred drug from the pharmacist and52.1% of students were usually followed these instructions, while the remaining did not truston pharmacist's instruction and followed specific drug's leaflet instructions. Conclusions:Over the counter medicines were widely practiced among students and tended to be higher instudents with a higher medical education. Students had an adequate knowledge regardingsafety and efficacy of these medications. Pharmacists play key role in advising and educatingconsumers on the correct use of these drugs. However, they must improve their clinicalknowledge and skills.